Spatio-temporal analysis of pulmonary tuberculosis in Astambul District, South Kalimantan, Indonesia 2020-2021 - Rosadi, Dian; Agustina, Novita; Haji Darise Lasari, Hadrianti; Fakhriadi, Rudi; Fadillah, Noor Ahda; Ali, Indra Haryanto (International Journal of Public Health Science (IJPHS), 2024)
Respiratory tuberculosis (TB) remains a significant global health concern and ranks among the top 10 leading causes of death worldwide, following human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). Globally, it is estimated that 1.2 billion people are at risk of being infected with tuberculosis, and Indonesia is the country that contributes the third-highest number of TB cases worldwide, behind China and India. Tuberculosis is still a significant issue in South Kalimantan, notably in Banjar Regency. This study is a descriptive study that intends to identify respiratory TB clusters spatially and temporally in Astambul District during 2020–2021 with the SatScan application, which is visualized as a map of respiratory TB clusters using the Quantum GIS 3.28 application. Data on respiratory TB cases collected from the Banjar District Health Office were examined using retrospective space-time scan statistics, employing a Poisson probability model for analysis. This study found 4 respiratory TB clusters, and 2 of them had significant results, namely in 2020 (RR=6.90, p-value=0.000030) and 2021 (RR=5.27, p-value=0.00003). Factors that affect these clusters are population density, the physical condition of houses, humidity levels, and the availability of health facilities.